When sex means survival stories of five months street-based, freelance sex workers in Iloilo City. - Cojuangco, Florenz Dean Q.
Using feminist standpoint epistemology that builds knowledge based on women?s experiences, this study presents and analyzes the everyday ealities of five women street-based, freelance sex workers in Iloilo City and their interpretations of these realities. The everyday realities refer to the women?s common patterns of survival, the major issues and challenges they face every day as street-based, freelance sex workers, the strategies that they develop or employ to respond to the issues and challenges. Primarily through Storytelling, Key Informant Interview (KII), participant observation and Focus Group Discussion (FGD), it was found out that in order to survive, they engage in sex work regularly. Some women also engage in other productive work to augment income from sex work. They also borrow money from fellow sex workers to meet the needs of their family. They also try their best to spend their money wisely and save whenever possible for emergency purposes. The women street-based, freelance sex workers try to maintain their good health through using condoms during sexual intercourse, taking dietary supplements, eating right, getting enough sleep, practicing proper hygiene and sanitation, and having regular checkup at the Social Hygiene Clinic.